2020
DOI: 10.36253/phyto-10772
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and pathogenic characterization of Cochliobolus anamorphs associated with common root rot of wheat in Azerbaijan

Abstract: Genetic variation among the Azerbaijani isolates of anamorphs of Cochliobolus spp., the causal agents of common root rot of wheat, was evaluated using pathogenicity assessments, sequence analyses of the internal transcribed spacer (ITS) region and glyceraldehyde-3-phosphate dehydrogenase (GPDH) gene, as well as inter-simple sequence repeat (ISSR) and inter-primer binding site (iPBS) markers. Twenty-eight isolates used in this study were obtained from diseased wheat plants in cereal growing regions of Azerbaija… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…e conidium sizes of the B. sorokiniana in barley examined in this study were consistent with that description from Sivanesan [18] and showed similar results to those obtained in previous studies by Samuels and Sivanesan [25], Agrios [2], and Özer et al [5,6].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…e conidium sizes of the B. sorokiniana in barley examined in this study were consistent with that description from Sivanesan [18] and showed similar results to those obtained in previous studies by Samuels and Sivanesan [25], Agrios [2], and Özer et al [5,6].…”
Section: Discussionsupporting
confidence: 93%
“…The conidium sizes of the B. sorokiniana in barley examined in this study were consistent with that description from Sivanesan [ 18 ] and showed similar results to those obtained in previous studies by Samuels and Sivanesan [ 25 ], Agrios [ 2 ], and Özer et al [ 5 , 6 ]. The conidium characteristics were useful criteria for the discrimination of B. sorokiniana isolates from other isolates due to their morphological similarities [ 5 , 6 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…sorokiniana . These findings imply that the distribution of individual species appears to be related to their adaptation to specific environments [ 16 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%